(untitled) (Bulletin KNOB, 2021)
Climate change and urbanization have substantial ramifications for the management and protection of cultural-historical landscapes. This is especially true for historical estate landscapes – landscapes whose character is defined by several historical castles, country houses (along with their gardens and parks), and landed estates – where climate change adaptation constitutes a major task. Issues of concern include an excess or shortage of water and changes to vegetation as a result of rising temperatures. That pressure is compounded by increasing urbanization and the associated recreational needs. These landscapes are also susceptible to spatial fragmentation due to urbanization, changes in ownership, changes in function, and so on. Combatting these pressures calls for a future-oriented design approach that deals sensitively with historically valuable landscape characteristics. It involves safeguarding the spatial quality of estate landscapes by striking a new balance between utility value (economic exploitation), amenity value (identity and familiarity), and future value (ecological sustainability). Such is the complexity of the task that a regional perspective is required in order to fully comprehend the cohesion and systemic relations between individual country estates and to develop a common basis for collaboration. This article proposes a landscape-based regional design approach aimed at understanding and designing future-proof estate landscapes. It details a preservation-through-development strategy based on spatial development in sympathy with historical landscapes structures in a process of meaningful stakeholder involvement. Key to this process is collaboration and co-creation with owners, experts, policy advisers and others. Design-based research is employed as a method for addressing the complex spatial tasks facing estate landscapes in an integrated and creative manner. Spatial design, at every level of scale, becomes a instrument for working out development strategies and principles for context-specific landscape formation. But also for highlighting possible solutions that can contribute to the protection and development of historical estate landscapes. In other words, this is not about opposing change or locking up the existing landscape, but about creating new landscape qualities through well-designed new developments. This coincides with a collaborative process in which stakeholders jointly weigh the pros and cons, learn and come up with solutions. The combination of substance, involvement and process makes the landscape-based regional design approach a powerful method for increasing the resilience and adaptability of the estate landscape and in so doing making this landscape future-proof.